Determinants of optimal antenatal care visit among pregnant women in Ethiopia: a multilevel analysis of Ethiopian mini demographic health survey 2019 data - Delelegn Emwodew Yehualashet; Binyam Tariku Seboka; Getanew Aschalew Tesfa; Tizalegn Tesfaye Mamo; Elias Seid (BMC, 2022)
Plain language summary Optimal antenatal care means attending at least four antenatal care visits during pregnancy. In Ethiopia, evidence on factors affecting the use of at least four antenatal care services has not been adequately documented. Using the 2019 Ethiopian Mini Demographic and Health Survey data, this study attempted to uncover factors associated with optimal antenatal care visits among pregnant women in Ethiopia. Data for women aged 15-49 who gave birth five years before the survey and attended antenatal care visits for their last pregnancy were taken from the 2019 Ethiopian Mini Demographic and Health Survey. Accordingly, 3927 women were included in the analysis. Coverage of optimal antenatal care visits is low among pregnant women in Ethiopia. In this study, only 43% of pregnant women received optimal antenatal care. Women's educational status, household wealth status, household size, mass media exposure, place of residence, and administrative region were associated with optimal antenatal care visits. Strategies to increase access and availability of antenatal care services are important, especially for communities in rural areas and disadvantageous regions. Financial assistance that allows mothers from poor families to access antenatal care services can be beneficial. Health promotion programs targeting uneducated mothers are important to raise awareness of the importance of receiving a minimum of four antenatal care services.